2013
DOI: 10.1007/s40037-013-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactive E-learning module in pharmacology: a pilot project at a rural medical college in India

Abstract: Many medical educators are experimenting with innovative ways of E-learning. E-learning provides opportunities to students for self-directed learning in addition to other advantages. In this study, we designed and evaluated an interactive E-learning module in pharmacology for effectiveness, acceptability and feasibility, with the aim of promoting active learning in this fact-filled subject. A quasi-experimental single-group pre-test/post-test study was conducted with fourth-semester students of the second prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 15 publications
(16 reference statements)
3
50
0
4
Order By: Relevance
“…[20] In pharmacology subject too, Gaikwad and Tankhiwale evaluated the effectiveness and acceptability of an interactive E-learning module in endocrine pharmacology among 2 nd year medical students. [7] Pre-and post-test scores showed that the intervention was moderately effective and well received. Similarly, Tse and Lo.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[20] In pharmacology subject too, Gaikwad and Tankhiwale evaluated the effectiveness and acceptability of an interactive E-learning module in endocrine pharmacology among 2 nd year medical students. [7] Pre-and post-test scores showed that the intervention was moderately effective and well received. Similarly, Tse and Lo.…”
Section: Discussionmentioning
confidence: 95%
“…[6] There have been generally positive student opinions reported in the small number of studies on blended learning in medical education and students' perceptions have varied considerably depending on the nature of online and face-to-face components, subject content and accessibility to computers. [7,8] Although blended learning has been well practiced, there are no studies which have assessed whether the reinforcement through E-learning should be provided before or after traditional teaching (imparted through didactic lectures) in the subject of pharmacology. Hence, we designed this study to develop and introduce E-learning models (ELMs) and blend them with conventional teaching-learning strategies at different time points and evaluate the perception of students toward them in addition to their performance.…”
Section: Introductionmentioning
confidence: 99%
“…The cases were subjected to multi-step peer review and published on the open-access internet platform. Gaikwad et al evaluated the effectiveness and acceptability of an interactive eLearning module in endocrine pharmacology among second year medical students [18]. Pre and post test scores showed that the intervention was moderately effective although there was also a high attrition rate.…”
mentioning
confidence: 99%
“…2. Students perceive eLearning systems easy to use and many interlinked subject matter can be presented and learnt in a comprehensive manner [7,15,18]. 3. eLearning contents can be accessed or provided to users on an as and when required basis [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation